IMPLEMENTATION OF PUBLIC SERVICE MANAGEMENT INFORMATION SYSTEMS TO SUPPORTING IMMIGRATION SERVICES IN THE IMMIGRATION OFFICE CLASS II NON TPI PEMALANG - Muhamad Rizqi Tsalis Fajar (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
The purpose of this research is to know factually about the implementation of the Public Service Management Information System (SIMPEL) to supporting Immigration services, especially in pre-applying for a Passport at the Immigration Office Class II Non TPI Pemalang in terms of SIMPEL quality, urgency of SIMPEL application and quality of information produced by SIMPEL. The method used is descriptive with a qualitative approach.. The results of this study indicate that the SIMPEL implementation is one of the efforts made by the Immigration Office Class II Non TPI Pemalang in providing the best Immigration service to the community, especially in pre-application for Passports. With regard to the quality of the system, SIMPEL is easy to use by users both for officers and applicants in pre-application for a Passport. The results of the SIMPEL implementation can also be directly felt by its applicant. Then in terms of the quality of the resulting information such as availability, easy to understand and understand, constraints, response time and accuracy can be said to be successful in its implementation. Then in terms of the urgency of SIMPEL, that the existence of SIMPEL at the Immigration Office Class II Non TPI Pemalang can provide benefits that can be obtained, both for the Immigration Office Class II Non TPI Pemalang, officers and the community (applicants).